The Effect of Cooperative Learning Model of Teams Game Tournament Type on Motivation and Learning Outcomes of Junior High School Students in Palu - Almagfira Almagfira; Lestari Alibasyahi; Raya Agni (CV. Dharma Samakta Edukhatulistiwa, 2024)
This study aims to explain the effect of Teams Game Tournament type cooperative learning model on motivation and learning outcomes of students in class VIII SMP Negeri 14 Palu. This type of research is a Quasi Experiment (pseudo experiment), the research design is a pretest-posttest nonequivalent group design . This research was conducted at SMP Negeri 14 Palu using two classes as research samples, namely the experimental class of 30 students and the control class of 31 students using the Random Sampling. Data collection use interviews, test questions, questionnaires. The research instrument uses teaching modules, test questions, questionnaires. The results of this study indicate that there is an effect of Teams Game Tournament type cooperative learning model on student motivation and learning outcomes. Based on hypothesis testing with the t test, the results of learning motivation are 0.000 <0.005 and learning outcomes of 0.000 <0.005 so that it has a significant effect. This can also be seen from the average value of learning motivation at the final meeting of the experimental and control classes. The experimental class had an average of 83% while the control class had an average of 62%. The average value of posstest learning outcomes of the experimental and control classes. The experimental class had an average of 82 while the control class had an average of 52. This shows that the use of the Teams Game Tournament type cooperative learning model can increase student motivation and learning outcomes.